Association of Serum Level and DNA Methylation Status of Brain-Derived Neurotrophic Factor with the Severity of Coronary Artery Disease - Tayyaba Batool, Maria Sarfraz, Syed Hyder Raza, Arooj Tahir, Rabbia Shabbir, Aneeqa Shahid (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Brain-derived neurotrophic factor (BDNF) has shown to promote myelination besides its effect on survival, differentiation, and plasticity of neurons. It has an important role in maintaining cardiovascular health in addition to its central nervous system function. The present study aimed to determine the serum level association with DNA Methylation status of brain derived neurotrophic factor with severity of coronary artery disease. Methods: This cross-sectional study was carried out on 164 major coronary artery patients in the department of Biochemistry & Pharmacology of Bahawal Victoria Hospital Bahawalpur from April 2022 to December 2022. Individual with possible cardiac symptoms such as chest pain and dyspnea were enrolled. Patients were distributed as CAD group (n=82) and non-CAD group (n=82). CAD severity was measured by Gensini scoring system. The coronary artery lumen stenosis was defined as follows: 1, 2, 4, 8, 16, and 32 was for 1-25%, 26-50%, 51-75%, 76-90%, 91-99%, and total occlusion respectively. Prior to angiography, patients’ anthropometric parameters such as BMI, systolic, and diastolic pressure were recorded. Demographic details such as age, gender, and smoking status were also noted. SPSS version 27 was used for data analysis. Results: Of the total 164 patients, there were 82 study group comprised of 58 (70.7%) male and 24 (29.3%) females whereas control group was comprised of 40 (48.8%) male and 42 (51.2%) females. Study group had at least one major coronary artery with > 50% stenosis classified as CAD group and non-CAD group patients had completely normal coronary angiographies. The CAD group patients had higher mean age and smokers than non-CAD group. The incidence of hypermethylated BDNF gene in CAD and non-CAD group was 86.6% and 70.7% respectively. There were insignificance difference of serum BDNF concentration mean values in CAD group (1.82 [1.61-2.12] ng/ml) versus non-CAD group (1.69 [1.39-2.03]). The BDNF methylation was found 81.2% in male and 83.4% in female patients. Regarding serum BDNF mean value, no significance difference was observed in men (1.82 [1.52–2.12]) and women (1.70 [1.44–2.02]). Conclusion: The present study concluded that the increased risk of CAD associated with BDNF hypermethylation may be useful for identifying subjects at risk. A significant correlation was also found between BDNF hypermethylation and CAD severity. There was no significant association between severity of CAD and BDNF serum level. Keywords: Brain-derived neurotrophic factor, serum level, Coronary artery disease, Severity, DNA methylation